Evaluasi Pemekaran 6 Provinsi di Papua: Studi Pandangan Tokoh Adat Papua - Samparisna Koibur (Syntax Corporation Indonesia, 2024)
The expansion policy regulated in Law Number 2 of 2021 mandates the formation of three new provinces in Papua, namely South Papua, Central Papua, and Mountainous Papua. They believe that expansion will bring more attention and resources to areas that have been neglected. The purpose of this study is to look at the impact of provincial expansion in Papua from the perspective of indigenous leaders, given that this policy has created six new provinces in the country. As part of the Indonesia government's efforts to improve administrative efficiency and accelerate development, these changes have generated a lot of response from the community, especially from indigenous Papuan leaders who have an important role in the country's social and cultural structure. This study uses a qualitative approach with literature review to reveal the subjective views and experiences of indigenous leaders related to provincial expansion. The results of the study show that traditional leaders support and oppose this expansion policy. Support comes from those who believe that expansion can accelerate progress and well-being, while objections stem from concerns that it could disrupt social and cultural stability. This research helps to understand the impact of expansion from the perspective of indigenous leaders, emphasizes that cultural and social aspects must be considered when making expansion policies, and suggests that an inclusive and local wisdom-based approach should be applied in Papua's development process.